Review of bioacoustical traits in the genus Physalaemus Fitzinger, 1826 (Anura: Leptodactylidae: Leiuperinae) - Hepp, Fábio; Pombal, José P. Jr. (Zootaxa, 2020)
Given the importance of acoustic communication in intraspecific recognition during mating activity, acoustic traits have been widely used to clarify the taxonomy of anurans. They have been particularly useful in the study of taxa with high morphological similarity such as the Neotropical genus Physalaemus. Here, we reviewed the acoustic repertoires of the species of Physalaemus based on homology hypotheses in order to make comparisons more properly applicable for taxonomic purposes. We covered all the known clades and species groups for the genus, analyzing 45 species (94 % of the currently recognized taxa). Different call types were labeled with letters (i.e., A, B, and C) to avoid speculative functional propositions for the call types. In order to identify correctly the observed frequency bands, we propose a method to interpret them based on the predicted graphic behavior on audiospectrogram and on the mathematic relationship among bands considering each kind of band production (e.g., harmonics and sidebands). We found different acoustic traits between the major clades P. signifer and P. cuvieri. Species in the P. signifer clade have more than one call type (67 % of species in the clade). Furthermore, all species of this clade have A calls with pulses and/or low fundamental frequency (< 500 Hz). In the P. cuvieri clade, species emit only one call type and, in most species, this call is a continuous whine-like emission with relatively high fundamental frequency (> 400 Hz) and several S-shaped harmonics (except for species of P. henselii and P. olfersii groups, P. centralis, and P. cicada). Within the P. signifer clade, pulsed calls are present in P. angrensis, P. atlanticus, P. bokermanni, P. crombiei, P. irroratus, P. moreirae, P. nanus, and P. obtectus, whereas within the P. cuvieri clade this feature is restricted to a few species (10 % of the clade): P. jordanensis, P. feioi, and P. orophilus. A principal component analysis of the quantitative data indicates two clusters that substantially correspond to the composition of these two major clades with a few exceptions. Overall, the cluster composed of taxa of the P. signifer clade has lower fundamental frequency, bandwidth and dominant frequency at the end of the call and higher frequency delta and dominant frequency at the end of the call than the cluster with most taxa of the P. cuvieri clade. We also identified and described several similarities among acoustic signals of closely related species, which might correspond to synapomorphies in the evolution of the acoustic signal in the group. Species of the P. deimaticus group emit long sequences of very short A calls with low fundamental frequency (< 300 Hz) and short duration (< 0.2 s). Most species in the P. signifer group have clearly pulsed calls and emit at least two different call types. Species in the P. henselii group have calls with only high frequency bands (> 1700 Hz). Species in P. cuvieri group have continuous calls that resemble nasal-like sounds or whines, with downward frequency modulation. Species in the P. olfersii group emit long calls (> 1 s) with ascendant and periodic frequency modulation. Calls of the species in the P. biligonigerus and P. gracilis groups usually have continuous whine-like calls with call envelopes very variable within species. In addition, we describe traits in the genus for the first time, such as complex traits not predicted by simple and linear acoustic models (nonlinear phenomena), and discuss the application of acoustic traits to taxonomy and phylogenetics and morphological constraints of the vocal apparatus that might be related to the different acoustic properties found.